Rapid characterization of oxidative deterioration in edible oil by optical photospectrometry - More, Pravin S.; Shelke, Anil V.; Late, Dattatray J. (Journal of Food and Dairy Technology, 2015)
This research work aimed to investigate the kinetic reaction of reused cooking oil and find the optimum conditions of its process. The feedstock was collected from the commercially available sunflower oil. Our investigation shows that the kinetic reaction of reused sunflower oil (auto-oxidation) obtained in terms of variation of absorption coefficient of unexposed sunflower as 0.05 while the exposed sunflower had 0.075. The optimum condition from optical absorption spectroscopy investigations were obtained as 0.267 for unexposed sunflower oil and 0.194 for exposed sunflower oil at room temperature. Furthermore, our FTIR spectroscopic results obtained are accurate and precise enough for such detection such as free fatty acid (FFA ~ 26%), acid ~ 53% and saponification ~ 192% get reduce in exposed oil was investigated.

Classification and study of near-surface region of active material for gas detection using x-ray photoelectron spectroscopy - More, Pravin S.; Late, Dattatray J.; Kondawar, Subhash B. (Advanced Materials Letters, 2016)
We report investigations on resistive material SnO2: Cu (9 wt. %) evaluated and optimized for the application of gas sensor. SnO2: Cu has been thoroughly characterized by using X-ray photoelectron spectroscopy (XPS). The deconvolution of XPS spectra confirms the existing surface reactive species in the form of states of the metal orbital and the presence of multiple pathways for the detection of CO vis-à-vis sintering temperature effect. Enhanced CO pickup at the sintering temperature of 650 0C (wide range and low sensitivity) and 750 0C (short range and high sensitivity) has been observed. The CO sensing and XPS data correlates well along with the nonconventional use of variation in average XPS background intensity of general scan seems to be related to optimized sensitivity conditions of various gases. Copyright © 2016 VBRI Press.